Archetypе images of fire and earth in the novels of I. Bagryany "Man running over the abyss "and E. M. Remark "Time to live and time to die " (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
In the article leading images of fire and earth are analyzed from the point of view of archetypal criticism in Ukrainian-German literary discourse of prosaic works about World War II. A place and value of these multidimensional archetypes are examined in the construction of space-time models of the compared works. The special attention is concentrated on their polysemantic and existential filling.
Keywords: archetype; archetypal criticism; existential